Alternative Approaches to Plastic Production and Recycling Policies - Boultadaki, Emmanouela; Koutsoukou, Theodora; Ratano, Francesco; Vatista, Ioanna; Vlachou, Eleni; Vogiatzi, Dimitra (HAPSc Policy Briefs Series, 2023)
Plastics offer convenience to businesses and the supply chain, but their improper disposal and low recycling rates pose significant environmental and health challenges. Each year, millions of tons of plastic end up in oceans, with a recycling rate below 9%. Thus, urgent action is required to tackle this global plastic crisis. This policy brief proposes a Europe-wide ban on colored plastics to promote a circular economy and enhance plastic recycling, drawing insights from successful recycling policies in Japan and South Korea. This approach, despite initial challenges, can yield long-term benefits such as reduced exports, energy conservation, and increased consumer awareness. Collaboration, funding, and material design innovation are key to promoting sustainable practices and combatting plastic pollution. By seizing this opportunity collectively, we can make a lasting impact in the fight against plastic pollution and address the climate crisis before it is too late.